Clinical, laboratory, and morphological characteristics of kidney damage in lymphoproliferative disorders - B. T. Dzhumabaeva; L. S. Biryukova; V. A. Varshavsky; S. A. Mar’ina; L. S. Roshchina; U. L. Julhakyan; E. S. Stolyarevich (Онкогематология)
Kidney involvement in the onset of lymphoproliferative diseases (LPD) detected rarely, observed mainly at tumor progression or relapse.Objective: to determine the clinical and morphological features of kidney damage in the initial manifestation of LPD.Materials and methods: 19 patients with LPD and kidney damage were included in the study. The diagnosis of non-Hodgkin’s lymphomas was established according to 2008 WHO classification. Histological and immunohistochemical, immunofluorescent and electron microscopic studies of nephrobiopsy have been performed.Results. Patients were aged 46-83 years (median 63 years), of which 13 were men and 6 women. Chronic lymphocytic leukemia / small cell lymphocytic lymphoma was established in 12 patients, marginal zone lymphoma – in 4 pts, follicular lymphoma – in 1 patient, Waldenstrom's macroglobulinemia – in 1 patient and diffuse large B-cell lymphoma (DLBCL) in 1 patient. Proteinuria was observed in 18 patients, microhematuria – in 6 pts, arterial hypertension – in 8 pts, nephrotic syndrome – in 3 pts and renal failure in 18 patients. The mean creatinine level was 330.9 ± 52.3 µmol/L, the average glomerular filtration rate was 25.7 ± 12.9 ml/min. Monoclonal IgMκ secretion was detected in 6 patients, BJκ protein – in 9 pts, increased free light chain level – in 4 pts, cryoglobulin – in 4 pts (type II cryoglobulin in 3 of them, type I – in 1 patient).Morphological study of nephrobiopsy revealed tumor lymphoid infiltration of kidney interstitium in 10 (52.6 %) cases. Diffuse small cell lymphoid proliferation was detected in 1 patient, local infiltration – in 9 pts, in 3 of them in combination with glomerulonephritis, and in 4 cases with kidney carcinoma. Local large cell lymphoid proliferation was found in 1 patient with DLBCL. Amyloidosis was detected in 2 pts and thrombotic microangiopathy – in 2 patients. Glomerulopathy was revealed in 10 patients (52.6 %): mesangioproliferative glomerulonephritis (MPGN) – in 4, mesangiocapillary glomerulonephritis – in 3, fibrillar glomerulonephritis (FGN) – in 1, immunotactoid glomerulonephritis – in 1, and glomerulonephritis with minimal changes – in 1 patient.Conclusion. Kidney damage in the onset of lymphatic tumor does not always manifest with proteinuria, hematuria, nephrotic syndrome and renal failure. In most cases, secretion of BJ protein, free light chains, monoclonal immunoglobulin and cryoglobulin are detected. Morphological changes are heterogeneous, including lymphoid proliferation, various types of glomerulopathies, amyloidosis and thrombotic microangiopathy.